IMPROVING THE PROCESS AND LEARNING OUTCOMES OF PANCASILA EDUCATION USING THE NUMBERED HEADS TOGETHER COOPERATIVE MODEL ASSISTED BY ANIMATION MEDIA - Riska, Riska; Abdulah, Abdulah; Avana, Nurlev (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This research was motivated by the low student participation and suboptimal learning outcomes in the Pancasila Education subject for Grade V students at SDN 130/II Pasir Putih. The learning process tended to be monotonous as it relied solely on textbooks, without the support of engaging instructional media. To address this issue, the study aimed to improve the learning process and student outcomes by implementing the cooperative learning model of the Numbered Heads Together (NHT) type assisted by animation media. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of two meetings, covering the stages of planning, implementation, observation, and reflection. The research subjects were 20 fifth-grade students. Data were collected through teacher and student activity observations, as well as learning outcome tests, and analyzed using both quantitative and qualitative methods. The results of the study showed a significant improvement in both the learning process and outcomes. Teacher activity observation scores increased from 76% in the first cycle to 95.8% in the second cycle. Student activity also improved from 70.8% to 91.7%. Furthermore, the number of students who achieved a score of ≥70 increased from 12 students (60%) in the first cycle to 17 students (85%) in the second cycle. Thus, it can be concluded that the implementation of the Numbered Heads Together model assisted by animation media is effective in enhancing the quality of the learning process and outcomes in Pancasila Education